2004
DOI: 10.1007/s00018-004-3470-z
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic origin of LI-cadherin revealed by protein and gene structure analysis

Abstract: The intestine specific LI-cadherin differs in its overall structure from classical and desmosomal cadherins by the presence of seven instead of five cadherin repeats and a short cytoplasmic domain. Despite the low sequence similarity, a comparative protein structure analysis revealed that LI-cadherin may have originated from a five-repeat predecessor cadherin by a duplication of the first two aminoterminal repeats. To test this hypothesis, we cloned the murine LI-cadherin gene and compared its structure to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 165 publications
5
30
0
Order By: Relevance
“…The observed splice donor and acceptor sites match, in general, the typical consensus sequences [44]. The mouse LI-cadherin gene [45] also consists of 18 exons but is, with nearly 59 kb, six times as large (Fig. 2).…”
Section: Gene Structure Comparison Of Ksp-and Li-cadherinsupporting
confidence: 57%
See 3 more Smart Citations
“…The observed splice donor and acceptor sites match, in general, the typical consensus sequences [44]. The mouse LI-cadherin gene [45] also consists of 18 exons but is, with nearly 59 kb, six times as large (Fig. 2).…”
Section: Gene Structure Comparison Of Ksp-and Li-cadherinsupporting
confidence: 57%
“…Besides the conserved structural features of both cadherins, the almost identical genomic organization is additional strong support for a common phylogenetic origin of Ksp-and LI-cadherin. We had previously shown that the intron positions within the region of the LI-cadherin gene encoding the cadherin repeats EC3 to EC7 almost perfectly match the respective regions of the classical E-, P-and N-cadherin genes encoding EC1 to EC5 [45]. The only differences are found in the second intron of EC4, which is slightly shifted and has a different phase, and in the region encoding the premembrane repeat (EC7), which contains an additional intron.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Cadherin-17 (CDH17) or liver intestine-cadherin (LI-cadherin) is a member of non-classical cadherin family [Jung et al, 2004], implicating its functional role in cell adhesion. Yet, CDH17 was initially identified as a proton-dependent peptide transporter-1 in human colon adenocarcinoma Caco-2 cells [Dantzig et al, 1994].…”
mentioning
confidence: 99%